KURANGNYA SUMBERDAYA DALAM MENGAWASI PRODUK PANGAN BERBAHAYA DI KECAMATAN SEKAYAM YANG DIHUBUNGKAN DENGAN UNDANG UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Methie Hadianti E.01109024 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Consumer protection in border area of Indonesia-Malaysia is not well implemented yet. It is indicated by the big amount of dangerous products in the market. The consumer right to get pleasure, security, and safety in consuming a product is not fully guaranteed. This study describes the problem about the lack of human resources, right, and facilities to control dangerous food product in district Sekayam, in related to the Consumer Protection Law. The method implemented in this study is qualitative approach with descriptive analysis. The result shows that there is inadequacy of POM human resources in implementing the regulation of consumer protection. It is caused by the scope of the duty is too wide, whereas the authority given to them is really limited on the controlling the food product distribution and taking the sample, besides the facility provided for POM is also inadequate. As the conclusion, it is needed to increase the number of POM human resources in order to improve the implementation of Consumer Protection Law, expand the authority of POM to do more duties such as doing sample test, and inform the society about the issues. In addition the facilities to support POM are also significantly needed to be improved. Key Words: Consumer Protection, POM Human Resources, POM Authority and POM Facility.